The Relevance between Theses Literature Reviews and Research Questions Written by Students of STKIP PGRI Sumatera Barat Graduated in 2019 - Yelfiza Yelfiza; Siska Siska (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This research aimed to investigate the relevance between the literature reviews and the research questions of the theses written by the students who graduated in 2019 from seven study programs in STKIP PGRI Sumatera Barat. The research design was qualitative research which focused on describing, explaining, and exploring the students' thesis writings, whether the literature reviews described were relevant to their research questions. Purposive sampling was the technique used to select the data that consisted of 13 students' theses. This research focused on those 13 theses because they were written in a qualitative method, which showed the relevance between research questions and the literature review. Here, content analysis was used to analyze the data to show whether the literature review of each thesis discusses the relevant theories to answer the research questions. The result showed that among 13 students' theses, 6 theses were relevant, and 7 were irrelevant. It means that more students had written with irrelevant theories. It can be suggested to the thesis advisors to give more attention to the quality of students' theses because the irrelevance can interfere with the qualities of their theses.